THE INFLUENCE OF PROBLEM-BASED LEARNING AND GROUP INVESTIGATION LEARNING MODEL ON CRITICAL THINKING SKILLS AND STUDENTS' LEARNING MOTIVATION - Rita Tipung Uvat; Didimus Tanah Boleng; Sonja Vera Tineke Lumowa (Program Pascasarjana Universitas Negeri Jakarta, 2021)
The purpose of this study was to examine the effect of the PBL and GI learning models on students' critical thinking skills and student's motivation. The procedure of the research used data collection methods with survey and test techniques (pretest and post-test). The data analysis techniques were researched instrument validation test, research instrument reliability, normality test, homogeneity test, One Way Anova test, and LSD Post-Hoc test. The results of the research using the PBL and GI learning models have a significant effect on critical thinking skills, a significant value of 0.00 < 0.0,5, and students' learning motivation gets a sig assessment. 0.00 < 0.05 which is stated to have a significant effect. Data testing was continued with the LSD Post-Hoc test to see a comparison of the effect of the use of the PBL learning model with the GI and the results were significantly different, namely the PBL model was a model that had more influence on critical thinking skills with a value of 0.039 <0.05 and on learning motivation with a value of 0.039 < 0.05. 0.046 < 0.05 compared to the GI model. The conclusion from this study is there is an effect of PBL and GI learning models on critical thinking skills and learning motivation of students of grade XII of WR Soepratman Catholic High School No. 020 Samarinda.